Faktor-Faktor Yang Memengaruhi Penerapan Metode Pembayaran Digital Pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Surakarta Dalam Menghadapi Era Revolusi Industri 4.0 - Iga Destya Putri; Aniek Hindrayani; Salman Alfarisy Totalia (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to analyze the determinants of the attitudes and intentions of UMKM in Surakarta City in implementing the digital payment system. This research is a quantitative descriptive research with 384 respondents as subjects of UMKM in Surakarta City who have implemented a digital payment system. The sampling technique was carried out using purposive sampling, namely MSMEs that have implemented digital payments. Data analysis technique using SEM-PLS. The results of the study show that perceived convenience influences perceptions of usefulness and attitudes of UMKM in Surakarta City in implementing payments. Next, the perception of expediency influences the attitudes and intentions of UMKM in Surakarta City in implementing digital payments. In addition, trust influences the attitudes and intentions of UMKM in Surakarta City in implementing digital payments. Finally, attitudes influence the intention of UMKM in Surakarta City to implement digital payments.